2019
DOI: 10.1097/sle.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Thymectomy for Large Thymic Cyst: Myasthenia Gravis With Thymoma Concealed by Thymic Cyst

Abstract: We herein report a case of myasthenia gravis (MG) in which thoracoscopic thymectomy was performed for a large thymic cystic lesion using a subxiphoid approach. We have previously suggested the usefulness of the subxiphoid approach in thymectomy. The indications of thoracoscopic thymectomy were recently expanded to include large thymic cystic lesions without intraoperative rupture of the lesions. The pathologic diagnosis of the lesion in the present case was multilocular thymic cyst with type A thymoma and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The authors do not describe any of the other characteristic features of MTC (lymphoid hyperplasia, cholesterol clefts), raising the question of whether this represents a true MTC. Yano et al 13 reported a MTC in which the authors documented a type A thymoma and a MNT. The authors did not go into detail describing the histologic appearance of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The authors do not describe any of the other characteristic features of MTC (lymphoid hyperplasia, cholesterol clefts), raising the question of whether this represents a true MTC. Yano et al 13 reported a MTC in which the authors documented a type A thymoma and a MNT. The authors did not go into detail describing the histologic appearance of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of inflammatory processes have been associated with development of these cysts, including: lupus ( 13 ), Sjogrens ( 18 ), Human immunodeficiency virus or HIV ( 19 - 21 ), surgery ( 22 ), immunoglobulin-G4 disease ( 23 ), and bacterial infection ( 24 ). Additionally, neoplastic processes associated with development of multilocular cysts are broad, and have included: Thymic carcinoma ( 12 , 15 , 25 ), Hodgkin’s lymphoma ( 26 , 27 ), Non-Hodgkin’s lymphoma ( 28 ), Langerhans histiocytosis ( 29 ), thymoma ( 15 , 30 , 31 ), papillary adenocarcinoma ( 32 ), seminoma ( 33 ) and, mature teratomas ( 34 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Robotic resection, although rare, has been utilized ( 65 ). Subxiphoid and transcervical approaches seem to be effective in selected patients with anterior midline location cysts with sufficient operator familiarity ( 9 , 23 , 31 , 66 ). Clamshell approaches have also been utilized ( 20 ) however are morbid and should be cautiously undertaken.…”
Section: Treatmentmentioning
confidence: 99%
“…The patient was able to be discharged home on postoperative day 3. Authors cite the improved visibility of bilateral phrenic nerves with this approach, particularly with the flexibility in moving the camera ( 37 , 38 ). Transcervical approach to thymectomy is largely discussed in the otolaryngology literature and has been successful for thymectomies as well as excision of parathyroid adenomas.…”
Section: Additional Approachesmentioning
confidence: 99%